The trade openness puzzle: insights into economic growth dynamics in ASEAN+3 economies - Nora Ria Retnasih (Faculty of Economics and Business, University of Muhammadiyah Malang, 2026)
This study aims to analyze the relationship between economic openness, as measured by trade index, import, export, gross capital formation, and economic growth, in the ASEAN+3 region during the period 2012-2022 using the Panel Vector Autoregression (PVAR) model. The results show that Gross Domestic Product (GDP) is significantly influenced by trade index, export, and import. In addition, exports are influenced by the trade and import index, while imports are influenced by the trade and export index. Gross capital formation is also found to have a significant effect on GDP, trade index, import, and export. However, this variable does not provide a causal effect on other variables in the model. These findings underline the strategic role of economic openness, especially international trade, in driving economic growth in the ASEAN+3 region. This study provides important insights into regional economic dynamics while emphasizing the importance of policies that support economic openness to strengthen regional economic integration and sustainable growth.